2010
DOI: 10.1063/1.3427221
|View full text |Cite
|
Sign up to set email alerts
|

Exergy analysis of particle dispersed latent heat thermal storage system for solar water heaters

Abstract: Phase change material (PCM) based latent heat thermal storage (LHTS) systems offer a challenging option to be employed as an effective energy storage and retrieval device if the energy source is intermittent and time dependent. However, the performance of LHTS systems is limited by the poor thermal conductivity of PCMs employed. The addition of high conductivity particles is proposed as one of the promising performance enhancement techniques for LHTS. In our study, an attempt is made to investigate the perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“…Using two PCMs can make an increase in the overall exergetic efficiency up to 19.0-53.8% compared with a single PCM [37] An appreciable enhancement in the exergy performance in the latent TES unit containing dispersed high conductivity particles in the PCM [27] The particles addition enhances the quality of recovered energy despite reducing the storage capacity of the unit. The higher heat transfer rates can minimize the exergy destruction.…”
Section: Effect Of Htf Mass Flow Ratementioning
confidence: 98%
See 3 more Smart Citations
“…Using two PCMs can make an increase in the overall exergetic efficiency up to 19.0-53.8% compared with a single PCM [37] An appreciable enhancement in the exergy performance in the latent TES unit containing dispersed high conductivity particles in the PCM [27] The particles addition enhances the quality of recovered energy despite reducing the storage capacity of the unit. The higher heat transfer rates can minimize the exergy destruction.…”
Section: Effect Of Htf Mass Flow Ratementioning
confidence: 98%
“…[42] Energy charge/discharge rate for parallel flow is 5% more than counter-current flow mode [43] PCM melting temperature, number and additives Temperature distribution during the freezing process has been investigated in detail [18] Both the efficiency and the percentage of stored latent energy increase by decreasing the PCM melting temperature. The energy efficiency of the system is strongly affected by the melting temperature [22] The PCM with lower melting temperature (paraffin) has the higher stored energy as compared with the PCM with higher melting temperature (P-wax) [23] From an energetic point of view, the transition temperature of the PCM should be as low as possible [24] A low transition temperature leads to an increased efficiency of the solar heat collection system [25] Muitiple-PCMs with reasonable arragements can achieve better charge-discharge performance [26] An appreciable enhancement can be achieved in the energy storage containing dispersed high conductivity particles in the PCMs [27] Effective thermal conductivity calculated by employing paraffin with lessing rings can be ten times greater than the thermal conductivity of paraffin) [44] Heat brush/PCM composite can be inferior to the fiber-chip/PCM composite in terms of heat transfer rate of the bulk but the former can be superior to the latter in terms of overall heat transfer rate [45] Flat plate PCM encapsulate can decrease the fan power consumption by 50%,response time much lower 50% [46] Inserting Carbon fiber brushes to PCMs can contribute to saving space and reducing the cost of the tanks [47] Inserting Carbon fiber clothes to the PCM can make a reduction in the thermal contact resistance and improve the heat exchange rate of the tank [48] Melting temperature difference between the multiple PCMs plays an important roles in storage performance [49] Energy charged-discharged in a cycle is 34.7% more when using five PCMs [50] Three PCMs can improve the receiver performance, reduce the fluid temperature fluctuation, and reduce the heat receiver weight [51] Three PCMs can have a higher phase change fraction and storage/discharge capacity [52] Storage unit dimension 2D directional measurements along the radial and angular directions are investigated to reveal the temperature variation for the TES performance [18] The total melting time of the PCM corresponding to cylindrical shell containers are considerably less than those of the rectangular containers having equivalent volume and surface area of heat transfer [29] Increasing shell diameter from 114 mm to 190 mm can cause an increase in the total stored energy ...…”
Section: Exergy Performance Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, exergy analysis depends on second law has been adopted by many researches (Erek and Dincer , 2009 ;Aghbalou and Badia, 2006) to overcome the inadequacy of energy analysis. Jegadheeswarm and Pohekar (2010) numerically analyzed the energy and exergy of a particle dispersed latent ESS. They found that the exergy analysis based on the performance evaluation of latent heat was more perspective measures than that of energy analysis and reflected the true potential of the system under different input parameters.…”
Section: Introductionmentioning
confidence: 99%